Gene profiling in breast cancer - Espinosa, Enrique (Henry Stewart Talks, 2009)
DNA microarrays and PCR can provide information about the biology of breast cancer, prediction of response and prognosis, A molecular taxonomy of breast cancer has been proposed based on gene profiling, Prediction of response is still inaccurate and further studies should be performed, Several prognostic profiles have proved advantage over classical prognostic factors, They could be used in the near future to select patients for adjuvant chemotherapy in breast cancer
Archived at 2021/02/25